Membran Berbasis Β-Trikalsium Fosfat Sebagai Membran Barier Pada Guided Bone Regeneration: Tinjauan Naratif - Maria Rini Wulan Dhari; Eddy Eddy; Rosalina Tjandrawinata; Tansza Permata Setiana Putri (Universitas Muhamadiyah Manado, 2026)
Guided Bone Regeneration (GBR) relies on a barrier membrane to prevent soft tissue invasion in the wound area and maintain space for bone formation. Conventional membranes generally function as a passive barrier without enhancing osteogenesis. Membranes fabricated with the addition of β-TCP were developed to enhance membrane bioactivity. This review aims to evaluate the role of β-TCP as a bioactive component in barrier membranes used in GBR procedures. The study used a narrative review approach with literature sources from PubMed, Google Scholar, and ScienceDirect in the period 2016–2026. The keywords used included “guided bone regeneration,